(3GddDdDI GdeVjFI aj GdYed HGdfSHg GdSJjfjIs - (3CHi GdaVGFd YR GdOjf YHO GdYRjR GdhaGFis; (3GdRfLGfj , YHO GdhgGH Hf EHQGgje Hf YHO GdhgGH GdNRQLj, YRGdOjf CHh GdaVGFd,J (B655 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3agPg QSGdg dWjag ai MSGH GdOQL hGdObGFb hSejJgG HGddDdDg GdeVjFI ai GdYed HGdfSHg GdSJjfjI dNUJgG ef QSGdJi GdeSeGg HfRgg GdWdGH s
(3BNQgG (B:s
(3aEf JSGhi GdeLPhQ agh UMjM hEdG aCYOg hGddg CYde jJdh LOhdG LfS NGQL GdVQH hLfS NGQL GdbSeI hgeG BNQ GdQSGdg s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B179 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B216s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B129 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B92 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs